The Effect of Incentives and Appreciation on Generation Z Productivity with Loyalty as a Mediating Variable: A Case Study in Surakarta City - Aqilla Fadya Haya Hakim; Irmawati Irmawati (Jurnal Economic Resource, 2026)
The purpose of this study is to ascertain and evaluate the impact of rewards and recognition on the productivity of Generation Z and to investigate the function of loyalty as a mediating variable in this connection. A total of 132 Generation Z workers in Surakarta City participated in the study, which used a quantitative methodology and a questionnaire. Structural Equation Modelling (SEM-PLS) utilising SmartPLS 4 was used for analysis. The findings showed that, whereas appreciation had a substantial positive effect on production, incentives had no discernible effect. Additionally, it was demonstrated that rewards and recognition had a strong positive impact on loyalty, thereby boosting productivity. Loyalty was found to mediate the effects of incentives and appreciation on productivity. These findings confirm that appreciation and loyalty play a significant role in increasing Generation Z productivity, while incentives have an indirect effect through increased loyalty.